2016
DOI: 10.3390/ijms17101603
|View full text |Cite
|
Sign up to set email alerts
|

Silver Nanoparticle-Mediated Cellular Responses in Various Cell Lines: An in Vitro Model

Abstract: Silver nanoparticles (AgNPs) have attracted increased interest and are currently used in various industries including medicine, cosmetics, textiles, electronics, and pharmaceuticals, owing to their unique physical and chemical properties, particularly as antimicrobial and anticancer agents. Recently, several studies have reported both beneficial and toxic effects of AgNPs on various prokaryotic and eukaryotic systems. To develop nanoparticles for mediated therapy, several laboratories have used a variety of ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
139
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 241 publications
(148 citation statements)
references
References 145 publications
(186 reference statements)
8
139
0
1
Order By: Relevance
“…Additionally, bacteria are less likely to develop resistance against Ag than against conventional antibiotics [19]. AgNPs have been widely used as antimicrobial agents against bacteria, fungi, and viruses [20,21]. AgNPs were reported as effective antibacterial agents against various gram-negative and gram-positive bacteria [22].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, bacteria are less likely to develop resistance against Ag than against conventional antibiotics [19]. AgNPs have been widely used as antimicrobial agents against bacteria, fungi, and viruses [20,21]. AgNPs were reported as effective antibacterial agents against various gram-negative and gram-positive bacteria [22].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, AgNPs exhibit a longer half-life in the brain than they do in other organs. Given this tendency of AgNPs to reside in the brain for an extended period of time, these particles and the related dissolved ions pose considerable neurotoxic hazards (Panyala et al, 2008, Zhang et al, 2016). …”
Section: Introductionmentioning
confidence: 99%
“…Ascorbic acid (AA), a key antioxidant in the central nervous system, is stored in glial reservoirs and released into the synaptic cleft, where it is taken up by neurons. In addition, AA scavenges ROS generated during synaptic activity and neuronal metabolism (Covarrubias-Pinto et al, 2015, Zhang et al, 2016). However, AA also has many other roles beyond acting as an antioxidant scavenger.…”
Section: Introductionmentioning
confidence: 99%
“…The reason for the variability in the biological responses of different cell lines is a very complex issue. 35 Finally, since it is known that the protein corona can affect NP behavior, including toxicity profile, we analyzed protein coronas of MSNPs after incubation in culture medium with serum. The results showed that the protein-corona composition changed with varying MSNP size.…”
Section: Analysis Of Msnp Protein Coronas By Sds-pagementioning
confidence: 99%